2023
DOI: 10.1166/jbt.2023.3236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hederin (Hed) on Alveolar Bone Microstructure During Tooth Movement in Rats

Abstract: Purpose: To discuss effects of Hederin (Hed) to tooth movement process in rats. Materials and methods: 54 rats were divided into Model and Hed groups at 7 d, 14 d and 21 d, establishment of rat tooth movement model, the Hed and Model group injected Hed [5 mg/(kg· d)] and equal volume normal saline intraperitoneally respectively, Take the medicine regularly every night. After 14 days, 9 rats in each group were killed, BV/TV, Tb. SP and trabecular number (Tb. N) were measured by Mirco CT. Using TRAP staining an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The effects of a specific COX-2 inhibitor called "Rofecoxib" and a conventional NSAID called "Diclofenac" were examined in relation to the suppression of TMO in rats. The results showed that both drugs significantly impeded dental motion, though partially in the context of Rofecoxib and completely in the [12] Hederin (Hed) Alveolar bone resorption During TMO, Hed may enhance the expression of RANKL and ADRB2 and encourage alveolar bone resorption. Herniyati H et al 2023 [13] Robusta coffee extract (Coffea canephora)…”
Section: Analgesicsmentioning
confidence: 99%
See 3 more Smart Citations
“…The effects of a specific COX-2 inhibitor called "Rofecoxib" and a conventional NSAID called "Diclofenac" were examined in relation to the suppression of TMO in rats. The results showed that both drugs significantly impeded dental motion, though partially in the context of Rofecoxib and completely in the [12] Hederin (Hed) Alveolar bone resorption During TMO, Hed may enhance the expression of RANKL and ADRB2 and encourage alveolar bone resorption. Herniyati H et al 2023 [13] Robusta coffee extract (Coffea canephora)…”
Section: Analgesicsmentioning
confidence: 99%
“…They function by blocking prostaglandin synthesis and calcium absorption in the intestines, which in turn causes a rise in resorption of bone and a direct reduction of osteoblastic activity. The majority of animal investigations found that the chronic group requiring long-term corticosteroid medication had an increase in tooth movement rate [12][13][14][15][16][17][18][19][20]. On the other hand, investigations on acute corticosteroid consumption revealed decreased bone turnover.…”
Section: Corticosteroids Immunosuppressive and Immunomodulatory Drugsmentioning
confidence: 99%
See 2 more Smart Citations